PERENCANAAN STRATEGIS CLOUD COMPUTING TECHNOLOGY BERBASIS Gafe (GOOGLE APPS For EDUCATION ) BAGI PERGURUAN TINGGI SWASTA DI WILAYAH III CIREBON PROPINSI JAWA BARAT - Enang Rusnandi; Deffy Susanti (STMIK Mardira Indonesia, Bandung, 2015)
Cloud Computing Technology is one of the technologies that can help facilitate the organization of activities related to the communication of data and information. For higher education, the need for the use of cloud computing technology is an urgent need that can be used as a support system that can support existing business processes, in addition to useful to smooth the process of data communication and information, both internally and externally. This research will be carried out aiming to obtain accurate information about what the strategy should be prepared colleges to adopt cloud-based technology GAfE (Google Apps for Education). This is necessary because the process of adopting these technologies require support, policies and measures are obvious.The target of this research will be the availability of guidelines and strategic roadmap on cloud computing technology in accordance with the conditions of private universities in the region III Cirebon of West Java Province. The plan of activities that will be conducted are to conduct an analysis of existing conditions in the private universities related to the needs of cloud computing technology by conducting a SWOT analysis, to obtain accurate information on the basis of the potential possessed, followed by an analysis of the forms of technology provided by GAfE that can be implemented by the private universities and finally made the strategic direction for private universities to be able to use cloud computing technology. Keywords: Cloud Computing Technology, Support System, GAfE, Analisis SWOT, Roadmap